2015
DOI: 10.1093/mnrasl/slv194
|View full text |Cite
|
Sign up to set email alerts
|

EXTraS discovery of an 1.2-s X-ray pulsar in M 31

Abstract: During a search for coherent signals in the X-ray archival data of XMM-Newton, we discovered a modulation at 1.2 s in 3XMM J004301.4+413017 (3X J0043), a source lying in the direction of an external arm of M 31. This short period indicates a neutron star (NS). Between 2000 and 2013, the position of 3X J0043 was imaged by public XMM-Newton observations 35 times. The analysis of these data allowed us to detect an orbital modulation at 1.27 d and study the long-term properties of the source. The emission of the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…We also note that Swift J0042.6+4112 could be an ultracompact binary (i.e., 4U 1626-67 and 4U 1822-37) with a white dwarf companion (Savonije et al 1986) that is under the HST detection limit. This kind of system has a hard power spectrum below 10 keV (see Esposito et al 2016), which is similar to Swift J0042.6+4112. We point out that this type of system has a very short orbital period (on the order of subhours).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…We also note that Swift J0042.6+4112 could be an ultracompact binary (i.e., 4U 1626-67 and 4U 1822-37) with a white dwarf companion (Savonije et al 1986) that is under the HST detection limit. This kind of system has a hard power spectrum below 10 keV (see Esposito et al 2016), which is similar to Swift J0042.6+4112. We point out that this type of system has a very short orbital period (on the order of subhours).…”
Section: Discussionmentioning
confidence: 77%
“…Recently, Esposito et al (2016) discovered the first accreting pulsar in the direction of an external arm of M31 with detection of its 1.2s spin, thanks to its relatively high pulse fraction (∼50%), using XMM-Newton observations. They also found that its orbital modulation is about 1.3 days.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first persistently accreting X-ray pulsar hosting a neutron star detected in M31 2 , and it also has the longest period among all known pulsars (rotation-powered and accreting) in globular clusters, being more than an order of magnitude slower than the mildly recycled accreting pulsar from Terzan 5 globular cluster (Papitto et al 2011). We note that this pulsar has also recently been detected by Esposito et al (2016), but these authors interpret the nature of this source quite differently. In this paper, we discuss possible evolutionary scenarios that may produce such slowly rotating neutron stars in globular clusters.…”
Section: Introductionmentioning
confidence: 64%
“…We note that when correcting photon arrival times using the orbital solution of Esposito et al (2016), we were only able to get sufficient pulsations significance in three observations (0112570101, 0650560301, 0690600401), whereas in all remaining datasets the pulsating signal was not detected because it was smeared. At the same time the orbital solution obtained in this study allows to significantly detect pulsations in all observations listed in Table 2.…”
Section: Refined Timing Analysismentioning
confidence: 85%
See 1 more Smart Citation